ANALISIS KEBUTUHAN AUDIT PEMBIAYAAN PERBANKAN SYARIAH - Muhammad Syafril Nasution (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Islamic banking is currently experiencing significant development due to the rapidprogress of the Islamic economy. Customers will increasingly use financialtransactions with Islamic banks. Islamic banks basically offer business financialproducts in accordance with Islamic sharia principles. Therefore, it is necessary tosupervise Islamic banking to carry out financing transactions in order to stick tosharia principles. Sharia Supervisory Board (DPS) as an institution that will strictlysupervise and ensure that banks will operate under sharia rules so that customershave confidence in sharia banks. DPS is tasked with providing an internal reporttogether with the external auditor every year. The audit of financial statements is themost crucial to ensure that the information provided will be used in decision making.The audit is carried out by an independent external auditor who is qualified inmanaging accounting. This may raise the question of whether it is relevant thatconventional auditors examine and produce audit reports for Islamic banks despitebeing professional and competent. Therefore, this paper will describe the role ofIslamic financial institutions related to the analysis of sharia audit needs. Aims tomaintain the corridor of sharia principles in the application of financing to Islamicbanking in Indonesia